Effects of the dietary supplementation of mixed probiotic spores of Bacillus amyloliquefaciens 54A, and Bacillus pumilus 47B on growth, innate immunity and stress responses of striped catfish (Pangasianodon hypophthalmus) - Thy, H.; Tri, N.; Quy, O.; Fotedar, Ravi; Kannika, K.; Unajak, S.; Areechon, N. (Academic Press, 2017)
The study used the mixed probiotics of Bacillus amyloliquefaciens 54A and B. pumilus 47B isolated from striped catfish (Pangasianodon hypophthalmus) intestine aiming to stimulate growth performance, innate immunity, stress tolerance of striped catfish. The average weight gain (AWG), specific growth rate (SGR), and feed conversion ratio (FCR) were analyzed after fish were fed the mixture of probiotics (B. amyloliquefaciens 54A and B. pumilus 47B) at concentrations of 1 108, 3 108, and 5 108 CFU g 1 feed for 90 days. Immunity parameters, survival rate of fish challenged with Edwardsiella ictaluri and ammonia tolerance were also investigated. The amounts of B. amyloliquefaciens and B. pumilus were counted and identified by specific primer pairs of Ba1-F/Ba1-R, and 16-F/Bpu-R to confirm the presence of probiotics in fish intestine. The AWG (476.6 ± 7.81 g fish 1) of fish fed probiotics at 5 108 CFU g 1 was significant higher than the control (390 ± 25.7 g fish 1) after 90 days of feeding, but there was no significant (P > 0.05) effect of probiotics on FCR and SGR. Fish fed diet containing probiotics at 5 108 CFU g 1 also expressed resistance to E. ictaluri infection and higher immune parameters such as phagocytic activity, respiratory bursts, and lysozyme activity than the control. Stress response with ammonia showed significantly lower mortality rate (25%, 20% and 27%) of fish fed probiotics at all three levels of 1, 3 and 5 108 CFU g 1 than the fish fed control diet (75%). The study also demonstrated that the probiotics survived in the intestine of striped catfish after 90 days of feeding. Therefore, the dietary supplementation of a mixture of B. amyloliquefaciens and B. pumilus at 5 108 CFU g 1 can be used to improve the health and growth rate of striped catfish.